Pemberdayaan Generasi Gen Z Melalui Kerajinan Tangan Tenun Ulos Tradisional sebagai Warisan Budaya Sumatera Utara - Hubertus Badodo Warwuwu; Charles Widianto Hulu; Krisman Jaya Nazara; Yusmalinda Yusmalinda; Fandra Dikhi Januardani (CV. Rumoh Aceh Publishing, 2026)
Empowering Gen Z in preserving local culture presents both a challenge and an opportunity in the digital era. One cultural heritage with high historical and philosophical value is the traditional Ulos weaving from North Sumatra. Ulos is not only a traditional Batak cloth but also a symbol of identity, prayer, and social values passed down through generations. However, interest in traditional crafts among the younger generation tends to decline due to globalization and technological advancements. This study aims to analyze strategies for empowering Generation Z through training and developing Ulos weaving skills as an effort to preserve culture while increasing economic independence. The method used is a descriptive qualitative approach using observation, interviews, and documentation techniques with youth groups in several Ulos artisan communities. The results show that integrating traditional weaving training with the use of digital media and technology-based marketing can increase the interest, creativity, and entrepreneurial spirit of Gen Z. Furthermore, collaboration between senior artisans, educational institutions, and local governments plays a crucial role in maintaining the sustainability of the program.